Competitive Position of Croatia at The Mediterranean Tourism Market - Pavlic, Ivana; Portolan, Ana (Mediterranean Journal of Social Sciences, 2012)
At the contemporary increasingly open and integrated world tourism market competitiveness measurements have become themost important indicators for receptive tourism countries worldwide. Almost every tourism country conception, strategies, policy and plancontain indicators of tourism country competitiveness. The main reason for lies on one hand in the high level of accessibility of almostevery tourism destination and on the other hand in the low capability of the tourism destination differentiation toward other competitors atthe tourism market. Every receptive tourism country, including Croatia, has been making constant efforts to achieve and sustain thecompetitive advantage. Therefore, the main aim of the paper is to determine, on the basis of the sampled indicators, the competitiveposition of Croatia at the Mediterranean tourism market among the selected nineteen direct and indirect competitors. An additionalpurpose is to offer directions to obtain a better market position and achieve long term competitive advantage. In order to gain insight intothe Croatian tourism position among the Mediterranean competitors, the paper contains consecutive indicators of the market share forthe analysed receptive tourism market: the real tourism share, proportional market share, index of penetration and coefficient of therelative competitiveness. Since competitiveness is a distinctly complex concept which is incessantly reflection of subjective observationsof qualitative features, for the purpose of the research indicators were used that applied quantification of the qualitative attributes andthat provide an objective comparison. The countries that are included in the research are, according to the indicators, at different levelsof economic and social development and also each of them operates at specific development level in different circumstances which arein any cases incompatible with another country that has completely different development level. Therefore the competitive analysis willbe based on description and factography.